A Content Analysis of Testosterone Websites: Sex, Muscle, and Male Age-Related Thematic Differences. Issue 2 (March 2018) - Ivanov, Nicholas; Vuong, Jimmy; Gray, Peter B.
Male testosterone supplementation is a large and growing industry. How is testosterone marketed to male consumers online? The present exploratory study entailed a content coding analysis of the home pages of 49 websites focused on testosterone supplementation for men in the United States. Four hypotheses concerning anticipated age-related differences in content coding were also tested: more frequent longevity content toward older men, and more frequent social dominance/physical formidability, muscle, and sex content toward younger men. Codes were created based on inductive observations and drawing upon the medical, life history, and human behavioral endocrinology literatures. Approximately half ( n = 24) of websites were oriented toward younger men (estimated audience of men 40 years of age or younger) and half ( n = 25) toward older men (estimated audience over 40 years of age). Results indicated that the most frequent content codes concerned online sales (e.g., product and purchasing information). Apart from sales information, the most frequent codes concerned, in order, muscle, sex/sexual functioning, low T, energy, fat, strength, aging, and well-being, with all four hypotheses also supported. These findings are interpreted in the light of medical, evolutionary life history, and human behavioral endocrinology approaches.